Ion beam excitation of TXRF yield - V.K, Egorov; E.V, Egorov; M.S, Afanas (Scientific transaction of the National University of Mongolia. Physics, 2022)
The work presents short discussion of TXRF and PIXE methods peculiarities. Taking into account of these peculiarities we realized the experimental scheme for TXRF measurements at ion beam excitation of characteristical fluorescence. The scheme is built on base of the planar X-ray waveguideresonator with specific design. Features of the new experimental method and parameters of ion beam analytical complex Sokol-3 used for the method realization are discussed.